(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2010)
Objectives: The objective of the study was to find out the incidence, indications, risk factors and outcomes of cases requiring relaparotomy following caesarean delivery during the puerperium. Material and Methods: This was a retrospective descriptive study set in a tertiary referral and teaching hospital ( Dhaka Medical College Hospital) in Dhaka, capital of Bangladesh. Results: Over a period of one year from January 1st to 31st December 2007, there were 3830 caesarean deliveries (48.43%) out of a total of 7909 deliveries. Relaparotomy was done in 24 patients (0.63%) of the caesarean sections. The indications of repeat laparotomy were secondary postpartum haemorrhage (PPH) in 11 cases(45.8%), primary PPH due to uterine atony in 8 cases (33%), uterine sepsis with haemorrhage in 1 case (4.17%), rectus sheath haematoma in 2 cases (8.3%), internal haemorrhage after caesarean section in 1 case (4.17%) and abdominal wound dehiscence in 1 case (4.17%). Of these 24 cases, in 4 cases, primary caesarean section was done in this institution while 20 had caesarean delivery at other hospitals and clinics at (5 cases) and outside Dhaka (15 cases). Main surgeries performed at relaparotomy were subtotal hysterectomy in 12 cases, total hysterectomy in 5 cases, drainage of haematoma and peritoneal toileting in 2 cases, resuturing of uterine incisions in 1 case, ligation of uterine vessels in 2 cases and internal iliac arteries in 1 case and others. More than one procedure was often performed in one case. There were 6 maternal deaths following relaparotomy caused by shock following PPH, septicaemia and internal haemorrhage. Conclusion: Repeat laparotomy within six weeks of caesarean delivery was required 1 in 200 cases in this institute. Case fatality rate was high (25%). Near miss fatalities were also common. Majority of these were preventable. Identification of risk factors, adequate attention during primary surgery, expert decision, prompt intervention and proper case management during relaparotomy will improve the outcome. Key words: Caesarean delivery; relaparotomy. DOI: 10.3329/bjog.v24i1.6319 Bangladesh J Obstet Gynaecol, 2009; Vol. 24(1) : 3-9